Quantification of liquid phase faecal odourants to evaluate membrane technology for wastewater reuse from decentralised sanitation facilities. Issue 1 (6th December 2018) - Mercer, E.; Davey, C. J.; Campo, P.; Fowler, D.; Williams, L.; Kolios, A.; Parker, A.; Tyrrel, S.; Walton, C.; Cartmell, E.; Pidou, M.; McAdam, E. J.
Abstract : A liquid phase method to treat faecal odourants at source using membrane technology, consequently encouraging facility and water reuse acceptance. Abstract : Public willingness to use decentralised sanitation facilities or arising water products is discouraged due to malodour, preventing improved sanitation practices or water reuse opportunities in low income countries. Whilst odour is characterised in the gas phase, it originates in the liquid phase. Consequently, controlling odour at source could prevent gas-phase partitioning and limit produced water contamination. This study therefore developed an analytical method for the quantitation of a range of liquid phase volatile organic compounds (VOCs) classified into eight chemical groups, known to be primary indicators of faecal odour, to provide characterisation of real fluids and to permit evaluation of several potential membrane separation technologies for liquid phase odourant separation. The gas chromatography mass spectrometry method provided quantitation in the range of 0.005 mg L −1 to 100 mg L −1 with instrument detection limits ranging from 0.005 mg L −1 to 0.124 mg L −1 . Linear calibration curves were achieved ( r 2 > 0.99) with acceptable accuracy (77–115%) and precision (<15%) for quantitation in the calibration range below 1 mg L −1, and good accuracy (98–104%) and precision (<2%) determined for calibration in the range 1–100 mg L −1 . Pre-concentration of real samples was facilitated via solid phase extraction. Subsequent application of the method to the evaluation of two thermally driven membranes based on hydrophilic (polyvinyl alcohol) and hydrophobic (polydimethylsiloxane) polymers evidenced contrasting separation profiles. Importantly, this study demonstrates the method's utility for liquid phase VOC determination which is of use to a range of disciplines, including healthcare professionals, taste and odour specialists and public health engineers.